A systematic review of strategies used to increase recruitment of people with cancer or organ failure into clinical trials: implications for palliative care research - Boland, Jason; Currow, David C.; Wilcock, Andrew; Tieman, Jennifer; Hussain, Jamilla Akhter; Pitsillides, Constantine; Abernethy, Amy P.; Johnson, Miriam J. (Elsevier, 2014)
Context. The challenges of palliative care clinical trial recruitment are well documented. Objectives. The aim of the study was to review tested strategies to improve recruitment to trials of people with a range of conditions who may access palliative care services but are not explicitly stated to be ‘‘palliative.’’ Methods. This was a systematic review with narrative description. The Cochrane, Embase, PubMed, PsycINFO, and CINAHL electronic databases were searched (English; January 2002 to February 2014) for quasi-experimental and randomized controlled trials (RCTs) testing the effect of recruitment strategies on accrual to clinical trials of people with organ failure and cancer. Titles, abstracts, and retrieved articles were screened by two researchers and categorized by recruitment challenge: 1) patients with reduced cognition, 2) those requiring emergency treatment, and 3) willingness of patients and clinical staff to contribute to trials. Results. Of 549 articles identified, 15 were included. Thirteen reported RCTs and two papers reported three quasiexperimental studies. Five were cluster RCTs of recruiting sites/institutions. One was a randomized cluster, crossover, feasibility study. Seven studies recruited patients with cancer. Others included patients with dementia, stroke, cardiovascular disease, diabetes, frail elderly, and bereaved carers. Some interventions improved recruitment: memory aid, contact before arrival, cluster consent, ‘‘opt out’’ consent. Others either reduced recruitment (formal mental capacity assessment) or made no difference (advance research directive; a variety of educational, supportive, and advertising interventions). Conclusion. Successful strategies from other disciplines could be considered by palliative care researchers. Tailored, efficient, evidence-based strategies must be developed, acknowledging that strategies with face validity are not necessarily the most effective.